A novel manoeuvre stability controller based on vehicle state prediction and intellectual braking torque distribution. (January 2020) - Zhang, Liqin; Wu, Yang; Li, Boyuan; Zhang, Bangji; Zhang, Nong
This paper proposes an innovative hierarchical direct yaw moment control strategy consisting of upper, middle and lower controllers. In the upper layer, a linear quadratic regulator metric based on current side-slip angle and predicted yaw rate is established to generate the controlled yaw moment. The middle layer determines the actuating tyre forces and allocates the required longitudinal forces for each tyre according to the current tyre–road contact condition. Furthermore, the desired longitudinal slip ratios for each tyre are calculated in the middle layer. Finally, a suitable brake pressure is achieved by the sliding mode controller in the lower layer. The simulation results of sine with dwell and double lane change verify the effectiveness of the proposed method. Compared with a traditional direct yaw moment control strategy that preferentially brakes the priority wheel, the proposed novel strategy is able to keep the longitudinal force of the tyre working in a linear region and has better robustness response when the tyre–road contact condition encounters sudden change.